2012
DOI: 10.1063/1.3675862
|View full text |Cite
|
Sign up to set email alerts
|

Probing band-tail states in silicon metal-oxide-semiconductor heterostructures with electron spin resonance

Abstract: We present an electron spin resonance (ESR) approach to characterize shallow electron trapping in band-tail states at Si/SiO2 interfaces in metal-oxide-semiconductor (MOS) devices and demonstrate it on two MOS devices fabricated at different laboratories. Despite displaying similar low temperature (4.2 K) peak mobilities, our ESR data reveal a significant difference in the Si/SiO2 interface quality of these two devices, specifically an order of magnitude difference in the number of shallow trapped charges at t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 14 publications
5
30
0
Order By: Relevance
“…9, 23 We found that it has similar characteristic to those of sample A, 5 but different characteristic from those of sample B. 5 This indicates that the effect of the charged impurities is not the dominated effect in sample B. Thus, we consider only the effect of the interface roughness in this work.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…9, 23 We found that it has similar characteristic to those of sample A, 5 but different characteristic from those of sample B. 5 This indicates that the effect of the charged impurities is not the dominated effect in sample B. Thus, we consider only the effect of the interface roughness in this work.…”
mentioning
confidence: 84%
“…This was applied to the three-dimensional electron gas 1,2 and to the 2DEG as in Si/SiGe 3 and MgZnO/ZnO. 4 Recently, there has been an experimental measurement on the bandtail states in Si/SiO 2 heterostructures at low temperature around 370 mK-3 K. 5 We showed in this paper that the existing semiclassical model gives incomplete description to the reported bandtail states. Then, we used path integral theory to suggest a function form of the low temperature bandtail states of a 2DEG with dense and random impurities, and provided much better description to the experimental data.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The "X" on the vertical axis on the right is the density of states in the lowest subband (two valleys) for a 2-dimensional system in silicon (after ref. 18). …”
Section: Discussionmentioning
confidence: 93%